Design and Implementation of Single Phase AC-DC Buck-Boost Converter for Power Factor Correction and Harmonic Elimination - Damodaran Jayahar; R. Ranihemamalini; K. Rathnakannan (Institute of Advanced Engineering and Science, 2016)
This paper discusses the Power Factor Correction (PFC) for single phase ACDC Buck-Boost Converter (BBC) operated in Continuous Conduction Mode (CCM) using inductor average current mode control. The proposed control technique employs Proportional-Integral (PI) controller in the outer voltage loop and the Inductor Average Current Mode Control (IACMC) in the inner current loop for PFC BBC. The IACMC has advantages such as robustness when there are large variations in line voltage and output load. The PI controller is developed by using state space average model of BBC. The simulation of the proposed system with its control circuit is implemented in MatLab/Simulink. The simulation results show a nearly unity power factor can be attained and there is almost no change in power factor when the line frequency is at various ranges. Experimental results are provided to show its validity and feasibility. Keyword